Pandemics - Doherty, P. C. (Peter C.) (Oxford : Oxford University Press, 2013)
"From HIV to H1N1, pandemics pose one of the greatest threats to global health in the twenty-first century. Defined as epidemics of infectious disease across large geographic areas, pandemics can disseminate globally with incredible speed as humans and goods move faster than ever before. While restricted travel, quarantine, vaccines, drugs, and education can reduce the severity of many outbreaks, factors such as global warming, population density, and antibiotic resistance will complicate our ability to fight disease. Respiratory infections like influenza and SARS spread quickly as a consequence of modern, mass air travel, while unsafe health practices promote the spread of viruses like HIV/AIDS and hepatitis C. In Pandemics: What Everyone Needs to Know, Nobel Prize-winning immunologist Peter Doherty addresses the history of pandemics and the ones that persist today, what promotes global spread, types of pathogens and the level of threat they pose, as well as how to combat outbreaks and mitigate their effects"--Provided by publisher.
Includes bibliographical references(p. 201-212).
Keywords: Pandemics -- history; Pandemics -- prevention & control; Disaster Planning; World Health; Print books